2000
DOI: 10.1002/(sici)1097-010x(20000101)286:1<49::aid-jez5>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Gonadal development and plasma steroid levels during pubertal development in captive-reared striped bass,Morone saxatilis

Abstract: Puberty is the period during which full sexual development occurs and the capacity to reproduce is acquired. Despite its importance, our understanding of the endocrine regulation of puberty in lower vertebrates is still limited. The objective of the present study was to describe the changes in gonadal development and plasma steroid levels in a relatively late maturing species, the striped bass, during the first four years of life. In about 65% of the females, puberty was initiated during the third year. Althou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 46 publications
3
41
0
Order By: Relevance
“…During spermiation, the cytoplasmic extensions of Sertoli cells became increasingly attenuated and appeared to break. After spermiation, the residual spermatozoa were reabsorbed by the Sertoli cells [25,64,77,78].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During spermiation, the cytoplasmic extensions of Sertoli cells became increasingly attenuated and appeared to break. After spermiation, the residual spermatozoa were reabsorbed by the Sertoli cells [25,64,77,78].…”
Section: Discussionmentioning
confidence: 99%
“…Holland et al [78,86] noticed an accelerated maturity in certain breeding fish, which, unlike those living in the natural environment, are not subjected to the effects of environmental variations (photoperiod, temperature, food availability). In an aquarium, Dabrowski et al [87] frequently observed Perca flavescens one year-old mature males, a phenomenon rarer in females.…”
Section: Discussionmentioning
confidence: 99%
“…Although not a focal point of other investigations, increased levels of androgens (generally testosterone, rather than 11-KT) during previtellogenesis have been reported in a number of fish species, such as striped bass, Morone saxatilis (Holland et al 2000) and seahorse, Hippocampus abdominalis (Poortenaar et al 2004). In females of other species, such as killifish, Fundulus grandis (Greeley et al 1988), channel catfish, Ictalurus punctatus (Kumar et al 2000) and sweep, Scorpis lineolatus (Dedual & Pankhurst 1992), elevated androgen levels during previtellogenesis were not obvious.…”
Section: Figurementioning
confidence: 99%
“…Mature males (n ¼ 8, GSI ¼ 4.2%) and females (n ¼ 10, GSI ¼ 2%) were sampled in January of their fourth year of age at their midgonadal development stage. More detailed information about the gonadal stages and seasonality was provided previously [50].…”
Section: Laser Capture Microdissection and Quantitative Rt-pcrmentioning
confidence: 99%